Diagnostic mediastinyscopy in pathology - Caruso, Enrique S.; Vasallo, Bartolomé C. (Cirugía del Uruguay, 1982)
The experience with diagnostic Carlens' mediastinoscopy is presented. During the 1975-81 period 225 mediastinoscopies were done, 74 (33%) as a diagnostic procedure, of them, in 55 cases for primary bronchopulmonary carcinoma, 8 for pulmonary metastasis and 5 for lynphomas. The exploration had histologic positive diagnosis in 39 /55 (70%) of cancer of the lung cases, 7 /8 of pulmonary metastasis and all of the 5 lynphomas. This resuts support the use of mediastinoscopy as a diagnostic procedure in neoplasic inoperable patiens without histologic confirmation. Even with mediastinal sindrome, with no serious complications.